PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN DESA WISATA AIK BUKAQ KECAMATAN BATUKLIANG UTARA KABUPATEN LOMBOK TENGAH - Ela Febriani; I Ketut Bagiastra; Wiwik Nirmalasari (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
This study discusses the participation of local communities in the development of the Aik Bukaq tourist village, the participation of local communities in the Aik Bukaq tourist village is still very minimal due to some potential that exists but has not been managed properly, people who still have negative perceptions about tourism affect the development of tourist villages, so also with Pokdarwis which is still lacking in embracing the community to be involved in tourism activities, the method used is a qualitative method. The results showed that the participation of local communities in the development of the Aik Bukaq tourism village was still not maximized, seen from 4 kinds of participation, namely participation in decision making, participation in implementation, participation in benefit-taking and participation in evaluation, the community was still not fully involved because they still thought that tourism activities can have a negative impact on society. The obstacles in the development of the Aik Bukaq tourist village are limited funds which resulted in obstacles in repairing, the 2018 earthquake which resulted in some facilities at tourist objects being damaged, and the lack of understanding of the Pokdarwis related to tourism.